A mouse model for pain and neuroplastic changes associated with pancreatic ductal adenocarcinoma - Selvaraj, Deepitha; Hirth, Michael; Gandla, Jagadeesh; Kuner, Rohini (Pain, 2017)
Pancreatic ductal adenocarcinoma (PDAC) continues to be one of the deadliest human malignancies and is associated with excruciating pain, which is a serious complication and severely impacts the quality of life in patients. In human patients, poor survival prognosis is linked to remarkable remodeling of intrapancreatic nerves, which, in turn, is correlated to increased pain intensity. Understanding mechanisms underlying pain associated with PDAC has been hampered by the lack of animal models which replicate all germane aspects of the disease and importantly, enable analyses of pain associated with PDAC. In this study, we describe an immunocompetent orthotopic mouse model of PDAC involving intrapancreatic growth of K8484 mouse PDAC cells, which reliably exhibits a large number of key characteristics of human PDAC, including its unique histopathology and neuroplastic changes. We observed that tumor-bearing mice demonstrated significant abdominal mechanical hypersensitivity to von Frey stimuli as well as on-going pain in the conditioned place preference paradigm. Moreover, a myriad of other behavioral tests revealed that indicators of overall well-being were significantly reduced in tumor-bearing mice as compared to sham mice. Morphological and immunohistochemical analyses revealed structural remodeling in several different types of sensory and autonomic nerve fibers. Finally, perineural invasion of tumor cells, a cardinal manifestation in human PDAC, was also observed in our orthotopic mouse model. Thus, we describe a validated tumor model for quantitatively testing hypersensitivity and pain in PDAC, which lays a crucial basis for interrogating tumor-nerve interactions and the molecular and cellular mechanisms underlying pain in PDAC.
Gesehen am 05.07.2018